Nutrition and exercise in the management of liver cirrhosis - Toshikuni, Nobuyuki (Baishideng Publishing Group Inc, 2014)
Liver cirrhosis (LC) patients often have protein-energy malnutrition (PEM) and decreased physical activity. These conditions often lead to sarcopenia, which is the loss of skeletal muscle volume and increased muscle weakness. Recent studies have demonstrated that PEM and sarcopenia are predictors for poor survival in LC patients. Nutrition and exercise management can improve PEM and sarcopenia in those patients. Nutrition management includes sufficient dietary intake and improved nutrient metabolism. With the current high prevalence of obesity, the number of obese LC patients has increased, and restriction of excessive caloric intake without the exacerbation of impaired nutrient metabolism is required for such patients. Branched chain amino acids are good candidates for supplemental nutrients for both obese and non-obese LC patients. Exercise management can increase skeletal muscle volume and strength and improve insulin resistance; however, nutritional status and LC complications should be assessed before an exercise management regimen is implemented in LC patients. The establishment of optimal exercise regimens for LC patients is currently required. In this review, we describe nutritional status and its clinical impact on the outcomes of LC patients and discuss general nutrition and exercise management in LC patients.